Pattern of admission and outcome of obstetric practices in a mission-based secondary healthcare facility in Ibadan, Nigeria. (2023)
Introduction and Objective: Poor obstetric outcomes in Nigeria with its attendant implications for measuring health indices have remained a significant health concern. The occurrence of adverse events due to unsafe care is a major contributor to the causes of maternal morbidity and mortality globally. The main objective of this study was to assess the pattern of admission as well as the outcome of Obstetrics practices in Oluyoro Catholic Hospital (OCH) Ibadan. Methodology: This was a retrospective, cross-sectional descriptive analysis of medical records of 194 cases managed between Janu-ary and December 2018. Using a proforma, data was obtained on obstetric characteristics of patients, indications for admission, outcome of pregnancy and the interventions received during patient's admission into the maternity ward. The socio-demographic characteristics were described sequentially with frequency tables and percentages. Chi-square statistics was used to determine the association between categorical variables at 5% level of statistical significance. Results: The mean age of the participants was 30.45 + 4.83 years and the majority, 183 (94.3%), of them were booked. Common indications for admission were onset of labour pains 74 (38.1%), and elective induction of labour 38 (19.6%). Two-fifths, 79 (40.7%) of the respondents had intrapartum augmentation of labour with oxytocin. The prevalence of episiotomy in this study was 22.2% while 5.2% had laceration. Majority, 182 (93.8%) had live babies out of which 8.2% required admission into the neonatal intensive care unit. Conclusion: Overall findings showed that the obstetric practices in the study setting were within the margin of acceptable standard and efforts to sustain the obstetric skills and practices of healthcare providers should be maintained.